Analisis Pengelolaan Dana Bantuan Operasional Satuan Pendidikan dalam Meningkatkan Mutu Pembelajaran di SDN 125 Balielo - Andi Nurwana; Nur Wahyudi; Kori Hartono; Asrul Jaya (Precise Journal of Economic, 2025)
This study aims to analyze the management of the Education Unit Operational Assistance Fund (BOSP) in improving the quality of learning at SDN 125 Balielo, Wajo Regency. The background of the study is based on the importance of effective, transparent, and accountable education fund management to support the creation of quality learning. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation involving the principal, treasurer, teachers, and the school committee as key informants. The results show that the management of BOSP funds at SDN 125 Balielo is carried out through three main stages: planning, implementation, and reporting. At the planning stage, the preparation of the School Activity and Budget Plan (ARKAS Application) is carried out in a participatory manner involving all school elements. At the implementation stage, funds are used to support learning operations, procurement of infrastructure, and payment of honorariums for non-ASN teachers. Meanwhile, at the reporting stage, the school strives to increase transparency by involving the school committee and using the ARKAS application in accordance with government regulations. Overall, BOSP fund management at SDN 125 Balielo plays a significant role in improving the quality of learning, as reflected in improved learning facilities, a smoother learning process, and increased student participation. However, increased treasurer capacity and better oversight are needed to ensure accountability and program sustainability.